2018
DOI: 10.7150/jca.25715
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal dedifferentiated liposarcoma: Analysis of 61 cases from a large institution

Abstract: Background: To describe the clinical features of retroperitoneal dedifferentiated liposarcoma (RP DDLS) and further evaluate the prognostic factors.Methods: The clinicopathological variables and treatment strategies of 61 RP DDLS patients who underwent surgical resections at a single institution between September 2005 and September 2016 were reviewed. Kaplan-Meier and Cox regression methods were conducted for survival analyses.Results: The average patients' age was 52 years (range, 27-81), and there was almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The is no consensus regarding the efficacy of radiotherapy and chemotherapy for retroperitoneal liposarcoma. Analysis of 61 cases of retroperitoneal liposarcoma at a large institution showed that response rates to radio-and chemotherapy are low, even with doxorubicin being the first-line chemotherapy for metastatic and or unresectable disease (48). Chemotherapy and radiotherapy are ineffective for the majority of PRPLS cases, with a chemotherapy response rate of <10% (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…The is no consensus regarding the efficacy of radiotherapy and chemotherapy for retroperitoneal liposarcoma. Analysis of 61 cases of retroperitoneal liposarcoma at a large institution showed that response rates to radio-and chemotherapy are low, even with doxorubicin being the first-line chemotherapy for metastatic and or unresectable disease (48). Chemotherapy and radiotherapy are ineffective for the majority of PRPLS cases, with a chemotherapy response rate of <10% (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Lehnert et al retrospectively analyzed 110 RSTS patients and found that intraoperative bleeding >1,500 mL was an independent risk factor for poor postoperative survival (13). Luo et al found that amongst retroperitoneal dedifferentiated liposarcoma (RP DDLPS) patients, higher levels of intraoperative bleeding predicted a poor survival prognosis [hazard ratio (HR) 3.302, 95% CI: 1.231-8.858, P=0.018] (14). In our study, univariate analysis revealed that intraoperative bleeding <1,500 mL indicated better OS and PFS, but the effect of multivariate analysis was not significant in PR RPLPS.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical resection of WDL and DDL remains the first choice, it remains an unsuitable option for patients with unresectable, unstable and metastatic disease, especially in those with large liposarcomas due to poor outcomes. It is clear there is much development to be made in this area, and until then prognosis remains poor with almost 50% of patients eventually dying with the disease [ 21 ]. In the meantime, an MDT approach to diagnosis and management is vital to providing the best outcome possible for such patients with this rare diagnosis.…”
Section: Discussionmentioning
confidence: 99%